Skin Diseases in Long‐Distance Runners - Henna Ahomies; Vincent Descamps; Stéphanie Leclerc‐Mercier; Nicolas Kluger (JEADV Clinical Practice)
ABSTRACT Long‐distance running, including both road running and trail/mountain running, has significantly increased in popularity in recent years. The prolonged, repetitive physical activity combined with environmental exposures predisposes runners to a range of dermatological problems. We reviewed the dermatological challenges faced by long‐distance runners, focusing on the prevalence, causes, and prevention of common skin conditions as well as risks related to ultra‐violet radiation. Understanding these skin conditions and the circumstances surrounding running is essential for prevention and effective management. We present the existing literature on (i) environmental, (ii) traumatic or mechanical, (iii) inflammatory and infectious skin diseases, and (iv) the exacerbation of pre‐existing dermatoses in long‐distance running. Special consideration is given to the risk of skin cancer due to ultra‐violet radiation and the photoprotection habits of endurance runners.